Spectrum Of Urodynamic Findings In Posterior Urethral Valve Patients Post Fulguration - Ahmad Mir , Tariq; Nissar , Shoaib; A baba , Aejaz; nazir mufti , Gowhar; Hameed, Raashid; Jan, Waseem; A Bhat , Nissar (Journal of Neonatal Surgery, 2024)
Background:Posterior urethral valve (PUV) is a common cause of urethral obstruction in children that can lead to end-stage renal disease (ESRD). Bladder-directed management (BDM) is a recent approach used to treat these patients. Our objective was to investigate the urodynamic abnormalities in PUV patients, analyse the changing patterns of urodynamic parameters in different age groups, establish a BDM strategy based on urodynamic study (UDS), and evaluate its impact on short-term functional outcomes. Materials and Methods: Patients of PUV, aged 3 – 18 years at time of inclusion, who underwent adequate fulguration at any age were enrolled in the study and a baseline UDS was performed. BDM was started based on the UDS findings and patients were followed regularly. A repeat UDS was performed after 6-12 months of treatment and the findings compared using standard statistical tools. Results: A total of 39 patients were included in the study. Initial UDS revealed hyperreflexia in 18 patients (46.15%), myogenic failure in 13 patients (33.33%), and small capacity bladder in 4 patients (10%). After BDM, improved bladder dynamics were observed in 22 patients (64.7%), worsening in 8 patients (23.5%), and no change in 4 patients (11.8%). Conclusion: This study supports the hypothesis that there is a natural progression of valve bladder dysfunction towards detrusor failure. Additionally, early detection of bladder abnormalities through UDS and the implementation of BDM may help prevent progression to myogenic failure after puberty...